Broadband Variable Radial Waveguide Power Combiner Using Multi-Section Impedance Matching Technique - Xu, Gang; Yang, Xue-Song; Li, Jia-Lin; Tian, Zhi-Ming (Applied Computational Electromagnetics Society Journal (ACES), 2021)
An L-band spatial variable radial waveguide power combiner with broad bandwidth and high power capacity is proposed. By adopting several techniques simultaneously, including multi-section impedance matching probes, grounded disc, and axial slots, the performance of the power combiner is improved. The parameters of the combiner are calculated, simulated and tested. It has a measured operation bandwidth ranging from 1.2 GHz to 2 GHz with VSWRs less than 1.4 at all ports. The extra insertion losses between the input ports and output port are less than 0.3 dB and the isolation between the input ports is better than 15 dB. The power capacity can reach 600 W and the combining efficiency achieves 90 %. The results from calculation, simulation, and measurement reasonably agree with each other.